2005
DOI: 10.1111/j.1523-1755.2005.00239.x
|View full text |Cite|
|
Sign up to set email alerts
|

Coronary calcification in hemodialysis patients: The contribution of traditional and uremia-related risk factors

Abstract: Coronary artery calcification is highly prevalent in the hemodialysis population and is associated with older age, higher BMI, inflammation and reduced trabecular bone volume. Higher OPG is independently associated with coronary artery calcification and may represent an incomplete self-defensive response to the progression of atherosclerosis in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
102
6
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 49 publications
15
102
6
6
Order By: Relevance
“…[6,12,15] A positive correlation between CRP and DCAC was detected, as in other studies. [13,15,17] Finally, a positive correlation between DCAC and CAC score at the beginning of the study was found, which is in accordance with the observed persistent CAC score progression. Multivariate analysis applied selectively in patients with positive DCAC in the end of the study (n=27) showed that DCAC was affected mainly by CAC0 and CaxP.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…[6,12,15] A positive correlation between CRP and DCAC was detected, as in other studies. [13,15,17] Finally, a positive correlation between DCAC and CAC score at the beginning of the study was found, which is in accordance with the observed persistent CAC score progression. Multivariate analysis applied selectively in patients with positive DCAC in the end of the study (n=27) showed that DCAC was affected mainly by CAC0 and CaxP.…”
Section: Discussionsupporting
confidence: 85%
“…This continuous CAC progression is in accordance with the findings of previous studies. [5,6,[10][11][12][13][14][15][16][17] CAC progression (DCAC) was not affected by a history of hypertension. Univariate analysis revealed that DCAC was not correlated with the amount of essential calcium intake administered as calcium bicarbonate during the study period, which is in disagreement with the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional biopsies were selected from previous clinical studies representing 10 CKD and 10 hemodialysis (HD) patients in which five of each category were diagnosed with HTO or LTO bone disease (Table 1). (36)(37)(38) CKD biopsies were from individuals with 24-hour creatinine clearance rates between 15 and 90 mL/m 2 who had not received phosphate binders, vitamin D analogues, or corticosteroids. (36) HD patients (stage 5) were 18 years or older, and had been on hemodialysis three times weekly for at least 3 months.…”
Section: Immunohistochemistry Of Human Bone Biopsiesmentioning
confidence: 99%
“…(36) HD patients (stage 5) were 18 years or older, and had been on hemodialysis three times weekly for at least 3 months. (37) The technique for immunohistochemical detection of bone proteins from clinical samples was adapted from a previously reported method. (39) In brief, two adjacent 5-mm sections of bone tissue were placed side by side on each slide.…”
Section: Immunohistochemistry Of Human Bone Biopsiesmentioning
confidence: 99%